Saberes tradicionais nos cursos de Pedagogia das universidades públicas do Estado de São Paulo - Mota, Maria Elizabete Pereira (Universidade Federal de São Carlos, 2026)
This dissertation investigates the presence and modes of incorporation of traditional quilombola and indigenous knowledge in the curricula of Pedagogy degree programs. The study is grounded in an anti-racist, decolonial, and contracolonial perspective, understanding the curricula as a field of political, symbolic, and epistemological disputes. Methodologically, this is a qualitative documentary research that analyzed the syllabi of mandatory courses on Education on Ethnic-Racial Relations (ERER), extracted from the Pedagogical Course Projects of public universities in the state of São Paulo. The results show that the incorporation of traditional knowledge occurs unevenly in the prescribed curricula. While indigenous knowledge appears explicitly named in all the syllabi analyzed, quilombola knowledge tends to be addressed implicitly, diluted within the field of Afro-Brazilian culture, being explicitly mentioned in only one of the courses. This asymmetry indicates epistemological limits in the recognition of this knowledge in initial teacher education. Although the presence of mandatory ERER courses constitutes a relevant condition for addressing these topics, it is observed that their mere existence does not guarantee the systematic valorization of traditional knowledge in the curricula. It is concluded that their effective incorporation requires political and epistemological choices that recognize them as legitimate forms of knowledge production, beyond their inclusion as complementary content, contributing to the construction of teacher education committed to anti-racist and contracolonial education.
Traditional knowledge in Pedagogy programs at public universities in the State of São Paulo
Keywords: Saberes tradicionais; Educação antirracista; Formação docente; Pedagogia; Educação das relações étnico-raciais; Traditional knowledge; Anti-racist education; Teacher training; Pedagogy; Education on ethnic-racial relations; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; 4. Educação de Qualidade; 10. Redução das Desigualdades; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável